Antibacterial Activity of Actinomycetes Isolates from The Rhizosphere of The Turate Kasumba Plant (Carthamus Tinctorius L.) Against Bacteria Causing Skin Infections - Safira Brigeeta Kinanti; Rachmat Kosman; Rusli Rusli (Universitas Muslim Indonesia, 2023)
Actinomycetes is one group of microorganisms capable of producing secondary metabolites that function as antibacterials. Actinomycetes isolates used were isolated from the rhizosphere of the kasumba turate plant (Carthamus tinctorius L.). The purpose of this study was to determine the antibacterial activity of Actinomycetes isolates from the rhizosphere of kasumba turate (Carthamus tinctorius L.) which is the largest and most against skin infection bacteria. The results of the study obtained 2 isolates that are most active. IARK-6 obtained spot with Rf value = 0.70 for Staphylococcus aureus bacteria, Rf1 = 0.70 and Rf2 = 0.38 for Staphylococcus epidermidis bacteria, Rf = 0.70 for Pseudomonas aeruginosa bacteria. While the results of KLT-Bioautography testing for isolate IARK-7 obtained spots with a value of Rf = 0.38 for Staphylococcus aureus bacteria, Rf = 0.70 for Staphylococcus epidermidis bacteria, Rf = 0.38 for Pseudomonas aeruginosa bacteria.